Drug utilization pattern of antihypertensive drugs in chronic kidney disease stage 5 patients in a tertiary care hospital of central India - Bharani, Kalpana; Bharani, Rajesh; Vohra, Rubina; Goyal, Chhaya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: India is experiencing a rapid health transition and is projected to become a major reservoir of chronic diseases like Diabetes and Hypertension and 25 to 40% of these subjects may develop chronic kidney disease and end stage renal disease. Aim and objective of the study was to analyze utilization pattern of antihypertensive drugs in chronic kidney disease patients in a tertiary care hospital. Methods: The present observational cross-sectional study was conducted in Sri Aurobindo Institute of Medical Sciences, Indore (M.P.) from 01.01.2018 to 31.03.2018 on patients with chronic kidney disease stage 5. The drug utilization pattern was studied with respect to age, sex, basic disease, duration of dialysis, type of antihypertensive used, etc. Comparison of mean between gender and dialysis / not on dialysis was done using unpaired ‘t’ test. A p value of < 0.05 was taken as statistically significant. Results: Of 198 patients, 63 (31.8%) were females and 135 (68.2%) were males, showing a male preponderance. Majority of the patients (54%) belonged to the age group 41-60 years. Majority of the patients were having diabetic nephropathy (40.9%), followed by CGN-CKD 5d (18.7%) and CIN-CKD 5d (17.2%). 11.6% patients were not on dialysis, while 88.4% were on dialysis with a mean duration of dialysis of 31.45±34.57 months. Calcium channel blockers were given in 87.4% patients, followed by centrally acting drugs in 56.1% patients, beta blockers in 51.0% and alpha blockers in 39.9%. 93.9% patients were on multidrug antihypertensive therapy. Mean number of antihypertensives required in patients on dialysis was lower than those not on dialysis (2.69±1.44 vs. 3.48±1.16, p <0.05), similarly mean number of antihypertensives use in males was higher than females (2.99±1.41 vs. 2.32±1.37, p <0.05). Conclusions: In order to treat CKD, it is important to treat hypertension as hypertension and CKD are related to each other. Treatment of hypertension will help in controlling future development of comorbidities. Calcium channel blockers and centrally acting drugs are the treatment of choice in patients with CKD stage 5D with hypertension. Multi-drug antihypertensive therapy is a better choice than mono/single-drug antihypertensive therapy.